Keski-Suomen digitaalisen sosiaali- ja terveyskeskus Omaks:n sähköisen asioinnin käytettävyystutkimus - Mäkiaho, Hanna (2023)
The costs of social and health care are increasing as the population ages and prevalence of illnesses increases, causing concern for the sustainability of public finances. Digital services are cost-effective ways to provide services, and social and health care cannot afford not to take advantage of the opportunities offered by digitalization. One of the most important requirements for digital social and health services is their usability. The purpose of this study was to investigate the experiences of service users, meaning customers, of the usability of electronic services in the Central Finland digital social and health care center Omaks. The research data was collected from those who had used Omaks’s chat or video meeting using an electronic questionnaire. The survey collected both quantitative and qualitative data through questions based on the System Usability Scale (SUS), independent variables, and open-ended questions. The research received a total of N = 247 responses, with n = 149 from chat users and n = 98 from video meeting users. There were N = 199 responses to open-ended questions. The data was analyzed according to the SUS survey’s own analysis guide, statistical tests of the SPSS program, and using data-driven content analysis. The research results showed that the usability of chat and video meeting was at a good level. However, the usability of chat was statistically significantly better than that of video meeting. Factors that improved the usability of chat included speed, clarity of queueing, and the ease of interaction. Factors improving the usability of video meeting included technology functionality, instructions received, and link to service. Both electronic services were hindered by technological challenges. Additionally, the usability of chat was negatively affected by long queue time, while the discoverability of the service was an issue in video meeting. According to the research results, there was a statistically significant correlation between age and the number of uses of chat's usability, but no such correlation existed for video meeting. Gender and the type of device used had no connection with chat or video meeting usability. The nurse service was statistically significantly better in terms of usability than the doctor service. There was no statistically significant difference in usability between different internet browsers. The topic of the thesis was relevant, and the research results are utilized in the development of digital services in the Central Finland wellbeing services county, supporting its strategic objectives by enhancing digitalized services.